Analysing farmers' learning for socio-ecological stewardship in Eastern Uganda: A transformative learning ecology perspective. Issue 1 (31st December 2023) - Misanya, Doreen; Tassone, Valentina C.; Kessler, Aad; Kibwika, Paul; Wals, Arjen E. J.
ABSTRACT: This paper analyses how smallholder farmers are learning for socio-ecological stewardship in a specific case study context in Eastern Uganda. The case under analysis is a watershed management project that uses an integrated farm planning (PIP) approach to strengthen farmers' stewardship capacities within the Manafwa watershed through interactive and dialogic ways of engaging and teaching farmers. Utilizing a transformative learning ecology (TLE) perspective, this study investigated features of the PIP approach that support transformative learning for socio-ecological stewardship in a rural context. Data was collected by interviewing eighteen farmers from different villages and PIP generations and all three PIP trainers of the project, and by observing training sessions as well as sensitisation workshops. As a main result, the study yielded new insights that can help enhance PIP-like learning configurations consisting of interconnected learning tenets, dimensions and processes. This enhanced learning configurating comprises an organic learning system that facilitates farmers to change their mindsets and redefine their values, perspectives, routines, and practices towards those that encourage socio-ecological stewardship. The TLE fostered by the PIP approach represents a useful heuristic that can guide and inspire both scholars and educators engaged in processes of cultivating socio-ecological stewardship in similar contexts.